Cosmetic surgery as a tool at the service of spectacle - Martorell, Sandra (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
More than twenty million cosmetic surgery procedures are carried out in the world each year. This figure, which is constantly on the rise, serves as a measurement of the impact of surgery on the celebrity-obsessed consumer society in which we live, lowering it to a level of banality that turns it into merely another consumer product. This study proposes an analysis of surgery as spectacle and of the success it represents for a public that is willing to go under the surgeon’s knife for the sake of periodic “upgrades” in the interests of conforming to the aesthetic standards dictated to us by the mass media.